ESG Confusion and Stock Returns - Berg, Florian,Koelbel, Julian F.,Pavlova, Anna,Rigobón, Roberto (National Bureau of Economic Research, 2022)
How does ESG (environmental, social, and governance) performance affect stock returns? Answering this question is difficult because existing measures of ESG perfor- mance – ESG ratings – are noisy and, therefore, standard regression estimates suffer from attenuation bias. To address the bias, we propose two noise-correction procedures, in which we instrument ESG ratings with ratings of other ESG rating agencies, as in the classical errors-in-variables problem. The corrected estimates demonstrate that the effect of ESG performance on stock returns is stronger than previously estimated: after correcting for attenuation bias, the coefficients increase on average by a factor of 2.6, implying an average noise-to-signal ratio of 61.7%. The attenuation bias is stable across horizons at which stock returns are measured. In simulations, our noise-correction pro- cedures outperform the standard approaches followed by practitioners such as averages or principal component analysis
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Nachhaltige Kapitalanlage; Corporate Social Responsibility; Impact Investment; Kapitalmarktrendite; Performance-Messung; IV-Schätzung; Environmental; social; and corporate governance; Instrumental Variables (IV) Estimation; Asset Pricing; Trading Volume; Bond Interest Rates; Environment and Development; Environment and Trade; Sustainability; Environmental Accounts and Accounting; Environmental Equity; Population Growth